2020
DOI: 10.1186/s13046-020-01595-x
|View full text |Cite
|
Sign up to set email alerts
|

TFEB-NF-κB inflammatory signaling axis: a novel therapeutic pathway of Dihydrotanshinone I in doxorubicin-induced cardiotoxicity

Abstract: Background: Doxorubicin is effective in a variety of solid and hematological malignancies. Unfortunately, clinical application of doxorubicin is limited due to a cumulative dose-dependent cardiotoxicity. Dihydrotanshinone I (DHT) is a natural product from Salvia miltiorrhiza Bunge with multiple anti-tumor activity and anti-inflammation effects. However, its anti-doxorubicin-induced cardiotoxicity (DIC) effect, either in vivo or in vitro, has not been elucidated yet. This study aims to explore the anti-inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 56 publications
0
40
0
3
Order By: Relevance
“…For example, in Cry ABR 120G-induced cardiac proteinopathy, TFEB overexpression can upregulate HSPB8 to restore normal desmin location ( 39 ). While in doxorubicin-induced cardiotoxicity, TFEB offered protection for dihydrotanshinone I against doxorubicin-induced cardiotoxicity by downregulating phosphorylation of inhibitor of κb kinase α/β and NF-κB ( 53 ). TFEB overexpression has also been shown to attenuate autophagosome buildup and mitochondrial fission in monoamine oxidase-A–induced HF ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Cry ABR 120G-induced cardiac proteinopathy, TFEB overexpression can upregulate HSPB8 to restore normal desmin location ( 39 ). While in doxorubicin-induced cardiotoxicity, TFEB offered protection for dihydrotanshinone I against doxorubicin-induced cardiotoxicity by downregulating phosphorylation of inhibitor of κb kinase α/β and NF-κB ( 53 ). TFEB overexpression has also been shown to attenuate autophagosome buildup and mitochondrial fission in monoamine oxidase-A–induced HF ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial damage can also initiate intracellular Ca 2+ imbalance [ 22 ], which further affects the apoptosis paths and causes myocardial cell death [ 23 ]. DOX also interferes with iron regulation [ 24 ], up-regulates NF-κB expression, which consequently causes the release of pro-inflammatory cytokines, i.e., tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), and interleukin-6 (IL-6), and triggers vascular and cardiac inflammatory reaction [ 25 ] and exaggerates their downstream apoptotic pathways [ 26 ]. In addition, oxidative stress activates several pro-fibrogenic factors, which enhances the accumulation of extracellular matrix and development of cardiac fibrosis [ 27 ], remodeling [ 28 ], and eventual cardiac dysfunction [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dihydrotanshinone I (DHT) is a natural compound extracted from Danshen. According to the reports, DHT has antitumor ( Allegri et al, 2021 ), anti-inflammatory ( Wang et al, 2020 ), and immunomodulatory effects ( Wang et al, 2020 ). Evidence has emerged that DHT attenuates crystalline silica–induced lung inflammation by regulating the immune response and inhibiting STAT1/STAT3 ( Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the reports, DHT has antitumor ( Allegri et al, 2021 ), anti-inflammatory ( Wang et al, 2020 ), and immunomodulatory effects ( Wang et al, 2020 ). Evidence has emerged that DHT attenuates crystalline silica–induced lung inflammation by regulating the immune response and inhibiting STAT1/STAT3 ( Wang et al, 2020 ). It has been reported that DHT could inhibit the activation of NF-κB induced by TNF-α ( Weng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%